Investigating Phenol Transport Using Copoly(Eugenol-DVB) 8% as a Carrier with the Supported Liquid Membrane Method - Agung Abadi Kiswandono; Windi Antika; Anisa Rahmawati; Rinawati Rinawati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
The presence of phenol in water has adverse effects on human health and the environment, as it is a toxic contaminant commonly found in industrial waste. To address this issue, studies were conducted to investigate the transport of phenol using copoly(eugenol-divinyl benzene) (Co-EDVB) 8% as a carrier on polytetrafluoroethylene (PTFE) membranes, employing the Supported Liquid Membrane (SLM) method. Various parameters affecting phenol transport were examined, including the pH of the source phase, concentration in the receiver phase, immersion time, carrier concentration, and transport duration. Co-EDVB 8% was synthesized through copolymerizing eugenol and 8% divinyl benzene, facilitated by the BF3O(C2H5) catalyst. The synthesized polymer was characterized using FTIR. The phenol concentration post-transportation was determined spectrophotometrically using a 4-aminoantipyrine reagent, with absorbance measured at λ = 456 nm. The findings indicate that under optimal conditions—source phase pH of 5.5, NaOH concentration of 0.1 M, immersion time of 1 hour, carrier concentration of 0.01 M, and a transportation time of 24 hours—the Co-EDVB carrier in the PTFE membrane efficiently transported phenol. Even after 24 hours of the phenol transport process, the percentage of membrane liquid loss (%ML Loss) did not significantly decrease, remaining at 8.35%. This was corroborated by Scanning Electron Microscope (SEM) results and FTIR characterization. In conclusion, the PTFE membrane incorporating 8% Co-EDVB as a carrier exhibits effective phenol transport, achieving a transportation efficiency of 92.10%.